A new genus of Psychodinae (Diptera, Psychodidae) from phytotelmata in a Honduran cloud forest - Bravo, Freddy; Cordeiro, Danilo; Jocque, Merlijn (Zootaxa, 2014)
Larvae of a new species of Psychodinae, Moruseodina cusucoensis gen. et sp. nov., were collected during a biodiversity survey of aquatic invertebrates in plant held water bodies (phytotelmata) in Cusuco National Park, Honduras. The fourth instar larva, pupa and adult male are described based on reared material. The new species was difficult to place in an existing genus, thus a new genus name is proposed. Based on similarities in morphological characteristics, ecology and distribution, the species Moruseodina superba comb. nov. and Moruseodina conspicua comb. nov. are transferred from Telmatoscopus Eaton, 1904 to the new genus.